The middle-sized church problems and prescriptions - Schaller, Lyle E. (Nashville,TN Abingdon, 1985)
Includes bibliographical references.
Companion volume to the author's The multiple staff and the larger church, and, The small church is different, which see also.
Keywords: Church management